2006
DOI: 10.1007/s00344-005-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum sp. Promotes Root Hair Development in Tomato Plants through a Mechanism that Involves Ethylene

Abstract: Tomato seeds were inoculated with the plant growth-promoting rhizobacteria Azospirillum brasilense FT326, and changes in parameters associated with plant growth were evaluated 15 days after inoculation. Azospirilla were localized on roots and within xylematic tissue. An increase in shoot and root fresh weight, main root hair length, and root surface indicated that inoculation with A. brasilense FT 326 resulted in plant growth improvement. The levels of indole-3-acetic acid (IAA) and ethylene, two of the phytoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 36 publications
7
43
1
7
Order By: Relevance
“…This was particularly demonstrated with Sp7 and Sp245 when inoculated by soaking, and Sp7 inoculation by drenching. This result somehow contradicts to the previous findings of Ribaudo et al (2006) who reported enhancement of IAA content of tomato shoots and roots due to A. brasilense FT 326 inoculation. However in cucumber, the level of endogenous IAA increased …”
Section: Effects Of Inoculation On the Level Of Endogenous Iaacontrasting
confidence: 99%
“…This was particularly demonstrated with Sp7 and Sp245 when inoculated by soaking, and Sp7 inoculation by drenching. This result somehow contradicts to the previous findings of Ribaudo et al (2006) who reported enhancement of IAA content of tomato shoots and roots due to A. brasilense FT 326 inoculation. However in cucumber, the level of endogenous IAA increased …”
Section: Effects Of Inoculation On the Level Of Endogenous Iaacontrasting
confidence: 99%
“…(Boiero et al, 2007). Ribaudo et al (2006) represented some of the efficient PGPR strains as the producer of different plant growth regulators. IAA-mediated ethylene production could increase root biomass, root hair number and consequently the root surface area of PGPR inoculated tomato plants.…”
Section: Plant Growth Promoting Rhizobacteriamentioning
confidence: 99%
“…PGPR have also been found to control or minimize phytopathogenic effects through niche competition, antibiosis and systemic resistance induction (Sturz & Christie, 2003;Zhou et al, 2015). Inoculation with Azospirillum brasilense FT 326 was shown to increase the tomato shoot and root fresh weight, main root-hair length and root surface area, thereby resulting in improved plant growth (Ribaudo et al, 2006). In contrast, pathogenic microorganisms could inhibit root growth by damaging beneficial microbes, secreting toxins and infecting the root system.…”
Section: Effects Of Inoculation With Rhizobacteria On Root Respiratormentioning
confidence: 99%